Two‐Stage Basilic Vein Transposition: Second Stage Results. Issue 1 (30th October 2017) - Rego, Duarte; Nogueira, Clara; Matos, António; Almeida, Paulo; Queirós, José; Silva, Fernanda; Sousa, Clemente; Almeida, Rui
Abstract: The increasing survival of hemodialysis patients results in the depletion of superficial venous capital justifying the use of the basilic vein. Many groups still prefer an arteriovenous graft due to transposition complexity and the time needed to achieve maturation. In this work we review the results of our series of basilic vein transpositions (BVT). BVTs were performed in two stages: first, creation of the fistula; second, transposition of the vein using three small incisions in the arm. All patients had to have direct arterialization of the basilic vein, therefore, patients with previous ipsilateral wrist fistulas also followed a two‐stage protocol. Data were retrospectively revised from all transposition procedures made between September 2005 and November 2012. Patency and complication rates were the primary outcomes evaluated. A total of 276 basilic veins were transposed. Usage rate was 82.2%. 8% ( N =  22) of the fistulas were never used due to thrombosis. Secondary patency rates at 1 and 2 years were, respectively, 84% and 66.3%. Complications occurred in 61.6% ( N =  170) of fistulas and 65.9% ( N =  112) of which had to undergo surgical or endovascular revision. The most frequent complication was vein stenosis (39.7% of late complications, N =  92). Albeit its greater technical complexity, the transposed basilic vein represents a hemodialysis access with good patency rates. Complication rates, although high, are less than those of CVC or prosthetic grafts. These results support the use of the transposed basilic vein as hemodialysis access after the brachiocephalic fistula.